STUDY OF ANTIBIOTIC RESISTANCE PATTERN OF CLINICAL ISOLATES (Baqai Journal of Health Sciences)
The antibiotic resistance pattern of the forty five clinical isolates (consisting of 33 Gram negative and 12 Gam positive bacteria) were determined, against nine antibiotics including streptomycin, gentamycin, neomycin, tetracycline, kanamycin, ampicillin, amoxicillin, chloramphenicol and vibramycin.